Malnutrition awareness and its determinants among Chinese older adults: findings from a cross-sectional survey - Fangzhou Li; Jingmei Zhang; Difei Wu; Xiyan Yu; Xujiao Chen (Frontiers in Public Health)
BackgroundMalnutrition is a prevalent but underrecognized health issue among older adults in China. Inadequate awareness may delay detection and intervention, especially in cognitively vulnerable populations. To assess the level of malnutrition awareness and its association with sociodemographic, cognitive, and nutritional factors in a representative sample of older Chinese adults.MethodsWe conducted a cross-sectional survey among 1,227 individuals aged ≥60 years in Zhejiang Province. Malnutrition awareness was measured using a validated 7-item questionnaire. Cognitive status, nutritional risk, frailty, sarcopenia risk, and fall risk were assessed using standard tools. Multivariate logistic regression was used to identify independent predictors of awareness.ResultsOverall, 49.1% of participants demonstrated adequate malnutrition awareness. While most recognized general nutrition concepts (93.5%) and protein supplementation (92.7%), awareness of psychosocial risk factors (e.g., depression) was limited (41.7%). Higher awareness was significantly associated with higher education (OR = 1.38, 95% CI: 1.23–1.55), cohabitation (OR = 1.33, 95% CI: 1.13–1.56), and better cognitive function (p < 0.0001). Age, BMI, and frailty were not independent predictors.ConclusionMalnutrition awareness among older Chinese adults remains suboptimal, particularly regarding psychological contributors. Targeted education strategies should be stratified by cognitive ability and living context to bridge awareness gaps and support national healthy aging initiatives.